2009
DOI: 10.1097/pas.0b013e3181957bc4
|View full text |Cite
|
Sign up to set email alerts
|

Expression Pattern of Claudins 5 and 7 Distinguishes Solid-pseudopapillary From Pancreatoblastoma, Acinar Cell and Endocrine Tumors of the Pancreas

Abstract: Solid-pseudopapillary tumor (SPT) of the pancreas is characterized by a discohesive appearance of the neoplastic cells. This has been linked to the displacement of E-cadherin and beta-catenin from their normal membrane location, which prevents adherens junctions to form. The nuclear localization of beta-catenin is also a feature of SPT that helps in differential diagnosis. This latter includes pancreatic endocrine tumor (PET) as SPT may show neuroendocrine differentiation, and pancreatic acinar cell carcinoma … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
34
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(40 citation statements)
references
References 29 publications
5
34
0
1
Order By: Relevance
“…Comper et al observed claudin-5 immunoexpression in all 20 SPN tested using conventional tissue sections [26]. We largely confirmed those observations, but 2/12 of our cases were claudin-5 negative and another 4 showed focal and/or weak staining.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Comper et al observed claudin-5 immunoexpression in all 20 SPN tested using conventional tissue sections [26]. We largely confirmed those observations, but 2/12 of our cases were claudin-5 negative and another 4 showed focal and/or weak staining.…”
Section: Discussionsupporting
confidence: 91%
“…SPN usually express β-catenin (nuclear stain), CD10, CD56, and PgR [24]. Claudin-5 was identified as a new marker of SPN, particularly useful in differential diagnosis of SPN and other 'solid cellular' neoplasms of the pancreas [26].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In paediatric PB patients, elevated AFP and CEA levels are the most common abnormal serological markers, and elevated AFP expression has been reported in ≤68% of cases (12,24,25,32), By contrast, these PB tumour markers are typically within the normal range in adult patients (1,3). Serum AFP levels may be used to monitor clinical response to therapy or recurrence in those patients whose tumors produce it (32).…”
Section: Discussionmentioning
confidence: 99%
“…In a study of a series of the rare pancreatic SPT (solid pseudopapillary tumour) Comper et al (2009) showed that claudin expression profile of this tumor is interesting when compared with claudin expression of the normal pancreas, PET (pancreatic endocrine tumour), ACC (pancreatic acinar cell carcinoma (ACC) and and PB (pancreatoblastoma ) and that the pattern of claudins 5 and 7 expression is highly specific in differentiating SPT from PET, ACC, and PB (Comper et al, 2009). …”
Section: Discussionmentioning
confidence: 99%